RELIGIOUS MODERATION IN PREACHING: THE RELEVANCE OF THE PSYCHOLOGY OF DAKWAH IN Q.S. THAHA: 43-44 IN THE MODERN ERA - Khair, Abul (Acta Islamica Counsenesia: Counselling Research and Applications, 2023)
This article aims to analyze the relevance of the psychology of da'wah found in the Qur'an in Thaha: 43-44 by means of preaching by preachers in modern times. This is urgent to study because the psychology of da'wah plays an important role in providing the effectiveness of da'i preaching in spreading Islam. This study uses a qualitative method by examining literature reviews, as well as commentary books that discuss Surah Thaha: 43-44. This research resulted in a conclusion that in Thaha: 43-44 there is a da'wah method, namely the qaulan layyina da'wah method. This method has something to do with the psychology of propaganda. The researcher also found that there is a relevance between the psychology of da'wah contained in Surah Thaha: 43-44 and the way da'i carry out preaching in modern times. This method will also remain relevant over time, due to the fact that all humans accept peace and reject violence.